2023
DOI: 10.1088/1361-6463/acc956
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of flow characteristics in a twin-surface dielectric barrier discharge reactor by Schlieren imaging

Abstract: Dielectric barrier discharges are an emerging technology for the plasma-catalytic removal of volatile organic compounds and other gas purification challenges such as the removal of O2 traces from H2. Packed-bed reactors are mainly used for these applications, but surface dielectric barrier discharges (SDBDs) typically printed on thin dielectric plates are promising alternatives for the treatment of large volumetric flow rates due to their low flow resistance causing a low pressure drop. Especially for SDBDs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The initial design was implemented by Offerhaus et al, [12] while Peters et al, [14] Schücke et al and Nguyen-Smith et al [15] characterized different aspects of the discharge, largely in the context of volatile organic compound oxidation. Additionally, Ollegott et al [6] investigated radial mass transport induced by the plasma discharge. The electrode configuration consisted of a thin α-Al 2 O 3 plate onto which two nickel-plated metallic grids were imprinted on opposite sides.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial design was implemented by Offerhaus et al, [12] while Peters et al, [14] Schücke et al and Nguyen-Smith et al [15] characterized different aspects of the discharge, largely in the context of volatile organic compound oxidation. Additionally, Ollegott et al [6] investigated radial mass transport induced by the plasma discharge. The electrode configuration consisted of a thin α-Al 2 O 3 plate onto which two nickel-plated metallic grids were imprinted on opposite sides.…”
Section: Methodsmentioning
confidence: 99%
“…(b) Photograph of the twin SDBD reactor setup with plasma ignition in N 2 . [6] SDBD, surface dielectric barrier discharge.…”
Section: Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale-up of this sDBD has been studied by Böddecker et al by combining 5 electrodes in parallel to treat up to 500 slm of gas [12]. The flow characteristic inside these sDBD has been investigated by means of the Schlieren imaging technique to analyze the flow pattern to assess the conversion as it depends on the gas flow and the plasma chemistry [13].…”
Section: Introductionmentioning
confidence: 99%
“…These experiments revealed that the gas conversion in these sDBD can be very large despite the fact that the plasma is located at the very electrode surface and fills the gas volume only to a very small extent. It has been observed [13] that the sDBD exerts a force on the gas, which induces a distinct flow pattern that leads to an efficient mixing of the gas and plasma species. This plasma-induced flow was triggered by the ion wind generated by the electric stray fields.…”
Section: Introductionmentioning
confidence: 99%